INTENTION TO VISIT RELIGIOUS DESTINATION: SUBJECTIVE NORMS, RELIGIOSITY AND ATTITUDE - Berto Mulia Wibawa; Rachma Rizqina Mardhotillah; Rizki Amalia Elfita (Journal of Halal Research, Policy, and Industry, 2022)
Indonesia is a country with the largest majority population in the world. Of the total population, about 86.9% of the population are followers of Islam. The high number of Muslims in Indonesia has increased the government's attention to developing the potential for halal tourism, one of which is religious tourism. This study aimed to determine the impact of religiosity, subjective norms attitude and intention to visit Sunan Ampel Surabaya. This research method uses quantitative methods using purposive random sampling techniques. Data collection used a questionnaire distributed to 150 Muslims in Surabaya who had never visited the Tomb of Sunan Ampel. The data obtained were then analyzed using Partial Least Square (PLS). The results of this study show that there is a significant positive influence between religiosity, subjective norms, attitude and intention to visit the Tomb of Sunan Ampel. The results of this study also explain that attitude can mediate subjective norms, religiosity and intention to visit.